2013
DOI: 10.3366/cor.2013.0033
|View full text |Cite
|
Sign up to set email alerts
|

Fighting words: a corpus analysis of gender representations in sports reportage

Abstract: In this study, we explore linguistic constructions of gender in US sports reportage concerning two related basketball altercations: the Pacers–Pistons NBA fight in 2004 and the Shock–Sparks WNBA fight in 2008. We use a combined corpus and qualitative textual analysis to investigate coverage from the days immediately following the fights and to compare that coverage to sports reportage more generally. Our analysis reveals key differences in narrative focus; for example, that NBA coverage is most interested in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Our research falls into the broad area of corpus-assisted or corpus-based discourse analysis, which is increasingly used to examine identity representations across media (e.g. Jaworska and Krishnamurthy, 2012;Baker et al, 2013;Hunt 2015) and, more recently, to explore the representation of sport and/or athletes, such as work by Aull and Brown (2013), Caple (2013), Jaworska (2016) and Jaworska and Hunt (2017). CADS utilises the quantitative tools of Corpus Linguistics to identify patterns of ideological interest in large bodies of language data.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Our research falls into the broad area of corpus-assisted or corpus-based discourse analysis, which is increasingly used to examine identity representations across media (e.g. Jaworska and Krishnamurthy, 2012;Baker et al, 2013;Hunt 2015) and, more recently, to explore the representation of sport and/or athletes, such as work by Aull and Brown (2013), Caple (2013), Jaworska (2016) and Jaworska and Hunt (2017). CADS utilises the quantitative tools of Corpus Linguistics to identify patterns of ideological interest in large bodies of language data.…”
Section: Methodology and Datamentioning
confidence: 99%
“…This study found that the concept of masculinity is referred to much more frequently overall, and that femininity is often represented focusing on the topic of gender differences and disparities (and not so often in more general texts). An analysis of linguistic constructions of gender in US sports reportage (basketball) revealed that reporting on the women's basketball league is always marked and thus contributes to the 'othering' of women and women athletes in sports news reporting (Aull, Brown 2013). Ismail (2016), investigating gendered keywords in Malaysian sports news discourse, moreover found the gender marking of sports competitions and associations and that female athletes are often associated with emotions.…”
Section: Related Work In Corpus and (Feminist) Discourse Studiesmentioning
confidence: 99%
“…Selittävänä tekijänä voisi olla esimerkiksi se, että miesten sarjojen pelaajat ovat yleensä katsojille tutumpia, minkä vuoksi pelaajien nimet nousevat useammin esiin selostuksen aikana (kulttuurisesta selitysmallista ks. Aull & Brown, 2013).…”
Section: Yhteenveto Ja Päätelmätunclassified
“…esim. Aull & Brown 2013;Billings, Halone & Denham, 2002;Campbell & Bebb, 2020;Kivelä, 2018). Molemmissa tutkimushaaroissa on havaittu runsaasti esimerkkejä hegemonisista rakenteista, joita urheilussa käytetty kieli rakentaa ja ylläpitää.…”
unclassified